Targeting pivotal amino acids metabolism for treatment of leukemia - Jiankun Hong; Wuling Liu; Xiao Xiao; Babu Gajendran; Yaacov Ben-David (Heliyon)
Metabolic reprogramming is a crucial characteristic of cancer, allowing cancer cells to acquire metabolic properties that support their survival, immune evasion, and uncontrolled proliferation. Consequently, targeting cancer metabolism has become an essential therapeutic strategy. Abnormal amino acid metabolism is not only a key aspect of metabolic reprogramming but also plays a significant role in chemotherapy resistance and immune evasion, particularly in leukemia. Changes in amino acid metabolism in tumor cells are typically driven by a combination of signaling pathways and transcription factors. Current approaches to targeting amino acid metabolism in leukemia include inhibiting amino acid transporters, blocking amino acid biosynthesis, and depleting specific amino acids to induce apoptosis in leukemic cells. Different types of leukemic cells rely on the exogenous supply of specific amino acids, such as asparagine, glutamine, arginine, and tryptophan. Therefore, disrupting the supply of these amino acids may represent a vulnerability in leukemia. This review focuses on the pivotal role of amino acids in leukemia metabolism, their impact on leukemic stem cells, and their therapeutic potential.